A Strategy of NIR Dual‐Excitation Upconversion for Ratiometric Intracellular Detection. Issue 22 (24th September 2019) - Ke, Jianxi; Lu, Shan; Shang, Xiaoying; Liu, Yan; Guo, Hanhan; You, Wenwu; Li, Xingjun; Xu, Jin; Li, Renfu; Chen, Zhuo; Chen, Xueyuan
Abstract: Intracellular detection is highly desirable for biological research and clinical diagnosis, yet its quantitative analysis with noninvasivity, sensitivity, and accuracy remains challenging. Herein, a near‐infrared (NIR) dual‐excitation strategy is reported for ratiometric intracellular detection through the design of dye‐sensitized upconversion probes and employment of a purpose‐built NIR dual‐laser confocal microscope. NIR dye IR808, a recognizer of intracellular analyte hypochlorite, is introduced as energy donor and Yb, Er‐doped NaGdF4 upconversion nanoparticles are adopted as energy acceptor in the as‐designed nanoprobes. The efficient analyte‐dependent energy transfer and low background luminescence endow the nanoprobes with ultrahigh sensitivity. In addition, with the nonanalyte‐dependent upconversion luminescence (UCL) excited by 980 nm as a self‐calibrated signal, the interference from environmental fluctuation can be alleviated. Furthermore, the dual 808/980 nm excited ratiometric UCL is demonstrated for the quantification of the level of intracellular hypochlorite. Particularly, the intrinsic hypochlorite with only nanomolar concentration in live MCF‐7 cells in the absence of exogenous stimuli is determined. Such an NIR dual‐excitation ratiometric strategy based on dye‐sensitized UCL probes can be easily extended to detect various intracellular analytes through tailoring the reactive NIR dyes, which provides a promising tool for probing biochemical processes in live cells and diagnosing diseases. Abstract : Near‐infrared (NIR) dye‐sensitized upconversion nanoprobes are designed for intracellular detection with high sensitivity and accuracy via a purpose‐built NIR dual‐laser confocal microscope system, providing a useful tool to study biological activities in live cells.